2010
DOI: 10.4274/jcrpe.v2i1.49
|View full text |Cite
|
Sign up to set email alerts
|

Al-Awadi/Raas-Rothschild Syndrome in a Newborn with Additional Anomalies

Abstract: Al-Awadi/Raas-Rothschild (AARR) syndrome is a rare phocomelia syndrome characterized by limb/pelvic hypoplasia/aplasia, renal anomalies such as horseshoe and polycystic kidney, and abnormal facial features including cleft palate, hypertelorism and micro-retrognatia. Autosomal recessive inheritance has been proposed for AARR syndrome. In this report a boy affected with AARR syndrome is presented. The previous pregnancy of the mother was terminated because of lower limb agenesis detected at 14th week of gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We also noted that these “occasional” manifestations are seen mostly in AARRS patients, and this may be also be related to the complete of loss‐of‐function of WNT7A . In the literature, Al‐Awadi syndrome has been given as a clinical diagnosis for patients with pelvic dysplasia/amelia of the lower limbs but with completely normal upper limbs [Alp et al, ]. Our review increases the awareness that WNT7A mutations will always have upper limb manifestations and hence such cases should not be labeled as Al‐Awadi syndrome.…”
Section: Discussionmentioning
confidence: 86%
“…We also noted that these “occasional” manifestations are seen mostly in AARRS patients, and this may be also be related to the complete of loss‐of‐function of WNT7A . In the literature, Al‐Awadi syndrome has been given as a clinical diagnosis for patients with pelvic dysplasia/amelia of the lower limbs but with completely normal upper limbs [Alp et al, ]. Our review increases the awareness that WNT7A mutations will always have upper limb manifestations and hence such cases should not be labeled as Al‐Awadi syndrome.…”
Section: Discussionmentioning
confidence: 86%
“…Based on the various associated clinical patterns of malformation, Phocomelia [4] [Table/ Fig-2]. Among the various aetiological factors attributed for the cause of this anomaly, thalidomide is a well known teratogenic drug which was prescribed under the label of Contergan and subsequently banned in 1960s [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in ESCO2 (establishment of cohesion 1 homolog 2) on 8p21.1 have been reported in Roberts/SC phocomelia [7]. Alp E et al, [4] reported a case of AARR syndrome in a male baby in a nonconsanguenous couple with additional anomalies, such as cryptorchidism, macrophallus and horseshoe kidney. Rao et al, [1] reported a 20 wk male stillborn fetus with with tetraphocomelia born to a mother with a negative history of consanguinity with additional feature of pelvic hypoplasia.…”
Section: Introductionmentioning
confidence: 99%